Cut-And-Fill Mining In Sweden: Development Trends And Applications - G. Almgren (Society for Mining, Metallurgy & Exploration, 1975)
With the exception of sublevel caving, the most common method of underground mining in Sweden is the "cut-and-fill" method. It is normally used for mining non-ferrous metals , and' is used extensively in the complex sulfide ore mines of the Boliden Company in north and central Sweden as well as the mines of the STORA and Vieille Montagne Companies in central Sweden. All in all, the cut-and-fill method is used in 13 of Sweden's 45 mines. As the mines are relatively small, the volume of ore mined by this method represents only about 5 % of the total ore production in Sweden. The commercial value, however, is much large than this percentage would imply. The production volumes and grades of some typical mines are shown in Table I. As seen, when rated internationally, the grades are comparatively low. The prices are set according to ?international metal prices? as dictated by the London stock exchange, and in lieu of governmental support, rational management methods are critical in order to achieve satisfactory profit.